The lack of resources as a contributory factor to the high failure rate in Standard 10 History examinations in the Alice circuit - Sobahle, Wellington Mkhululi (Rhodes University, Faculty of Education, Department of Education, 1988)
As the title of this thesis indicates, the researcher was concerned at the high failure rate in the Standard 10 history examinations in the Alice circuit. This problem is confined neither to history as a subject nor to a single area in the Ciskei.
Keywords: History -- Study and teaching (Secondary) -- South Africa; Black people -- Education -- South Africa